2020
DOI: 10.1177/2473011420966311
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Multicenter, Clinical and Radiographic Evaluation of a Biointegrative, Fiber-Reinforced Implant for Proximal Interphalangeal Joint Arthrodesis

Abstract: Background: A novel biointegrative implant was developed for proximal interphalangeal joint (PIPJ) arthrodesis to treat hammertoe deformity. Composed of continuous reinforcing mineral fibers bound by bioabsorbable polymer matrix, the implant demonstrated quiescent, gradual degradation with complete elimination at 104 weeks in animal models. This prospective trial assessed the implant’s safety, clinical performance, and fusion rate of PIPJ arthrodesis for hammertoe correction. Methods: Twenty-five patients (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The results of this preclinical study are aligned with the results of a recent prospective study using mineral fiber-reinforced implants for proximal interphalangeal joint arthrodesis in humans. 44,45 Although tissue reaction was not assessed by histopathology in this human study, no adverse tissue response was reported on magnetic resonance imaging, and implant biointegration was optimal at the 2 years.…”
Section: Discussionmentioning
confidence: 85%
“…The results of this preclinical study are aligned with the results of a recent prospective study using mineral fiber-reinforced implants for proximal interphalangeal joint arthrodesis in humans. 44,45 Although tissue reaction was not assessed by histopathology in this human study, no adverse tissue response was reported on magnetic resonance imaging, and implant biointegration was optimal at the 2 years.…”
Section: Discussionmentioning
confidence: 85%